Visual attention and emotional responses to photovoltaic-green facades from a street-walking perspective - Haolin Du; Chunying Li; Jiayu Wang; Haida Tang; Yuanli Lyu; Wenjie Liu (Energy and Buildings, 2026)

Three-dimensional numerical simulation of sandstone failure characteristics based on mineral particles and pore structure - Dong Duan; Haolin Guo; Jiahan Zhu; Xiaojing Feng; Xiaoyu Chen; Shibin Tang; Yingjie Xia; Weiheng Guo (Bulletin of Engineering Geology and the Environment, 2026)

Effects of artificial reefs on the spatial and temporal distribution and ecological niche dynamics of rockfish (Sebastes spp.): an integrated analysis using environmental DNA and species distribution models - Yongjun Shang; Haolin Yu; Liyou Zhang; Tao Zhang; Yanli Tang (Fisheries Science, 2026)

A proton-relay strategy with K-modulated N/P proton pairs over Ru-based catalysts for efficient ammonia decomposition - Shuyu Chen; Rui Chen; Liang Wang; Haibo Tang; Rui Wang; Tian Tian; Yawei Zhou; Zihan Meng; Haolin Tang (Chemical Engineering Journal, 2026)

Fluoride-ion mediated radical scavenging in a hydrophobic microenvironment for durable PEM fuel cells - Xuelin Wei; Gang Zhu; Donghao Ye; Aojie Zhang; Hao Zhang; Wangkai Zhu; Tian Tian; Shengqiu Zhao; Jiangping Song; Rui Chen; Haolin Tang (Chemical Engineering Journal, 2026)

Porous polybenzimidazole membrane with enhanced phosphoric acid retention derived from incorporation of confined metal organic frameworks for high-temperature proton exchange membrane fuel cells - Yaohu Li; Shiying Tu; Guoliang Liu; Hongfei Pan; Yun Jia; Wenbo Lou; Haolin Tang; Haining Zhang (Chemical Engineering Journal, 2026)

Superacid polymer electrolyte with end-group-protected proton sites mitigates ammonia poisoning for efficient electrochemical hydrogen separation from ammonia cracking reformate gas - Jiaqi Shuai; Hao Li; Zhengrui Xiao; Zeqi You; Yucong Liao; Rui Wang; Yafeng Li; Yuanwei Yan; Jiangping Song; Tian Tian; Lan Zhang; Siew Hwa Chan; et al. (Chemical Engineering Journal, 2025)

Dioxole-contained perfluorosulfonated ionomers with different equivalent weights as catalyst binder and proton conductor for proton exchange membrane fuel cells - Cairong Wang; Yao Tong; Yadong Wang; Haolin Tang; Haining Zhang (Fuel, 2025)

Plasma engineering defect for constructing high-density Ru single atoms and RuCo alloy nanoparticles synergistic catalytic system to achieve efficient hydrogen evolution - Haolin Zeng; Yingchun Guo; Tongtong Li; Guangliang Chen; Jinfeng Qiu; Bin He; Peisong Tang (Chemical Engineering Journal, 2025)

Modulation of Ryanodine Receptors on Microglial Ramification, Migration, and Phagocytosis in an Alzheimer’s Disease Mouse Model - Yulin Ouyang; Zihao Chen; Qiang Huang; Hai Zhang; Haolin Song; Xinnian Wang; Wenxiu Dong; Yong Tang; Najeebullah Shah; Shimin Shuai; Yang Zhan (Neuroscience Bulletin, 2025)

Selective recovery of tin and lead from waste photovoltaic solder ribbon with acetic acid leaching - Qing Huang; Haolin Zhang; Zhijie Tang; Hongyan Yan; Xiaogang Li; Jianming Zhu; Lijun Xu; Wenyi Yuan (Chemical Engineering Journal, 2025)

Atomized potassium-assisted hydrogen generation from ammonia decomposition over ruthenium loaded carbon-based catalysts - Qi Li; Hongfei Pan; Xiege Huang; Wei Xi; Wenmao Tu; Haining Zhang; Haolin Tang (Chemical Engineering Journal, 2025)

Functionalized pyrite carrier enhances Anammox biofilm formation and nitrogen removal efficiency: Carrier modification, interface regulation, and metabolic activation - Tingting Liu; Peng Gao; Dongyue Li; Xin Zhang; Peng Tang; Linzhu Du; Haolin Niu; Mengqi Gao; Jun Li; Yuhan Zhu; Zehao Zhang (Chemical Engineering Journal, 2025)

Efficient hydrogen conversion of toluene via biochar-supported Fe-Cu bimetallic catalyst under CO2-steam synergistic conditions - Jiankai Zhang; Xinjia Wang; Hui Jin; Jinzheng Wang; Haofeng Yang; Cong Dong; Guoneng Li; Yuanjun Tang; Haolin Liu; Chao Ye (Journal of Environmental Chemical Engineering, 2025)

RTDETR-MARD: A Multi-Scale Adaptive Real-Time Framework for Floating Waste Detection in Aquatic Environments - Baoshan Sun; Haolin Tang; Liqing Gao; Kaiyu Bi; Jiabao Wen (Journal of Marine Science and Engineering, 2025)
Accurate and efficient detection of floating waste is crucial for environmental protection and aquatic ecosystem preservation, yet remains challenging due to environmental interference and the prevalence of small targets. To address these limitations, we propose a Multi-scale Adaptive Real-time Detector (RTDETR-MARD) based on RT-DETR that introduces three key innovations for improved floating waste detection using unmanned surface vessels (USVs). First, our hierarchical multi-scale feature integration leverages the gather-and-distribute mechanism to enhance feature aggregation and cross-layer interaction. Second, we develop an advanced feature fusion module incorporating feature alignment, Information Fusion, information injection, and Scale Sequence Feature Fusion components to ensure precise spatial alignment and semantic consistency. Third, we implement the Wise-IoU loss function to optimize localization accuracy through high-quality anchor supervision. Extensive experiments demonstrate the framework’s effectiveness, achieving state-of-the-art performance of 86.6% mAP50 at 96.8 FPS on the FloW dataset and 49.2% mAP50 at 107.5 FPS on our custom water surface waste dataset. These results confirm RTDETR-MARD’s superior accuracy, real-time capability, and robustness across diverse environmental conditions, making it particularly suitable for practical deployment in ecological monitoring systems where both speed and precision are critical requirements.

In-situ transformation and synergistic electrocatalysis of asymmetric threefold hollow sites in rosebud-like ternary metal diselenide - Shihao Wang; Lin Liao; Jinsong Wu; Haolin Tang; Haining Zhang (Chemical Engineering Journal, 2025)

Design, synthesis and systemic acquired resistance of 2-benzothiadiazolylquinoline-4-carboxamides by COI1 based virtual screening - Xiaoyu Liu; Hongwei Yang; Yaru Sun; Yuting Huang; Shuang Hong; Haolin Yuan; Wei Gao; Liangfu Tang; Zhijin Fan (Molecular Diversity, 2025)

Graphene quantum dots decorated organic conductive polymer for advanced ternary amorphous solar-blind UV photovoltaic photodetectors - Han Cai; Haolin Yang; Weisen Li; Jiarong Liang; Zhuogeng Lin; Xingui Tang; Yanghui Liu; Dan Zhang; Wei Zheng (Chemical Engineering Journal, 2025)

Exploring the influence of different precursor materials on the catalytic performance and deactivation characteristics of iron-loaded biochar catalysts for the catalytic cracking of toluene - Jinzheng Wang; Chao Ye; Haofeng Yang; Zefu Ye; Zhujun Zhu; Haolin Liu; Hui Jin; Xinjia Wang; Jiankai Zhang; Guoneng Li; Yuanjun Tang; Qinhui Wang (Science of The Total Environment, 2024)

Exploring the impact of fulvic acid on electrochemical hydrogen-driven autotrophic denitrification system: Performance, microbial characteristics and mechanism - Haolin Chen; Meiyi Tang; Liang He; Xinxin Xiao; Fei Yang; Qiulai He; Shiquan Sun; Yang Gao; Lean Zhou; Yifu Li; Julong Sun; Wei Zhang (Bioresource Technology, 2024)

Adsorption-desorption of copper(II) by temperature-sensitive nano-biochar@PNIPAM/alginate double-network composite hydrogel: Enhanced mechanisms and application potentials - Haolin Chen; Yiwei Pan; Wei Zhang; Anlin Long; Mengqi Chen; Xinxin Xiao; Ziyi Wang; Meiyi Tang; Yazhou Peng; Shiquan Sun; Huining Zhang; Qiulai He (Chemical Engineering Journal, 2024)

Mechanism study of toluene removal using iron/nickel bimetallic catalysts supported on biochar - Haofeng Yang; Chao Ye; Jinzheng Wang; Hui Jin; Jiankai Zhang; Xinjia Wang; Cong Dong; Guoneng Li; Yuanjun Tang; Guanqun Luo; Haolin Liu; Xingping Fang; et al. (Science of The Total Environment, 2024)

Proton exchange membranes with functionalized sulfonimide and phosphonic acid groups for next-generation fuel cells operating at 120 °C - Yucong Liao; Shengqiu Zhao; Guoliang Liu; Hao Li; Jiaqi Shuai; Letian Wang; Bingxuan Liu; Haolin Tang (Chemical Engineering Journal, 2024)

Confined tuning of the charge distribution of Pt electrocatalyst for reinforcing anti-poisoning ability: Toward efficient separation of hydrogen from gases containing ammonia - Changqing Jin; Fanglin Wu; Haibo Tang; Hongfei Pan; Zhida Chen; Rui Wang; Zihan Meng; Junsheng Li; Haolin Tang (Chemical Engineering Journal, 2023)

Trehalose-enhanced ionic conductive hydrogels with extreme stretchability, self-adhesive and anti-freezing abilities for both flexible strain sensor and all-solid-state supercapacitor - Haolin Cai; Dongzhi Zhang; Hao Zhang; Mingcong Tang; Zhenyuan Xu; Hui Xia; Kangshuai Li; Jun Wang (Chemical Engineering Journal, 2023)

Polyphenol synergistic cerium oxide surface engineering constructed core-shell nanostructures as antioxidants for durable and high-performance proton exchange membrane fuel cells - Shengqiu Zhao; Yucong Liao; Rui Wang; Guoliang Liu; Haining Zhang; Haolin Tang (Chemical Engineering Journal, 2023)

Tailoring the acidity of WO3/ZrO2 to regulate the energy barrier of water dissociation in alkaline hydrogen evolution - Jiankun Wei; Jia Wang; Wei Guo; Haolin Tang; Junsheng Li (Chemical Engineering Journal, 2023)

Effects of habitat usage on hypoxia avoidance behavior and exposure in reef-dependent marine coastal species - Haolin Yu; Guangjie Fang; Kenneth A. Rose; Jiazheng Lin; Jie Feng; Haiyan Wang; Qingxian Cao; Yanli Tang; Tao Zhang (Frontiers in Marine Science, 2023)
Reef habitat in coastal ecosystems is increasingly being augmented with artificial reefs (ARs) and is simultaneously experiencing increasing hypoxia due to eutrophication and climate change. Relatively little is known about the effects of hypoxia on organisms that use complex habitat arrangements and how the presence of highly preferred AR habitat can affect the exposure of organisms to low dissolved oxygen (DO). We performed two laboratory experiments that used video recording of behavioral movement to explore 1) habitat usage and staying duration of individuals continuously exposed to 3, 5, and 7 mg/L dissolved oxygen (DO) in a complex of multiple preferred and avoided habitat types, and 2) the impact of ARs on exposure to different DO concentrations under a series of two-way replicated choice experiments with or without AR placement on the low-oxygen side. Six common reef-dependent species found in the northeastern sea areas of China were used (i.e., rockfish Sebastes schlegelii and Hexagrammos otakii , filefish Thamnaconus modestus , flatfish Pseudopleuronectes yokohamae , sea cucumber Stichopus japonicus , and crab Charybdis japonica ). Results showed that lower DO levels decreased the usage of preferred habitats of the sea cucumber and the habitat-generalist filefish but increased the habitat affinity to preferred habitat types for the two habitat-specific rockfishes. Low DO had no effect on the crab’s habitat usage. In the choice experiment, all three fish species avoided 1 mg/L, and the rockfish S. schlegelii continued to avoid the lower DO when given choices involving pairs of 3, 5, and 7 mg/L, while H. otakii and the flatfish showed less avoidance. The availability of ARs affected exposure to low DO for the habitat-preferring rockfishes but was not significant for the flatfish. This study provides information for assessing the ecological effects and potential for adaptation through behavioral movement for key reef-dependent species under the increasing overlap of ARs and hypoxia anticipated in the future.

Catalytic cracking and catalyst deactivation/regeneration characteristics of Fe-loaded biochar catalysts for tar model compound - Haolin Liu; Chao Ye; Zefu Ye; Zhujun Zhu; Qisong Wang; Yuanjun Tang; Guanqun Luo; Wenwen Guo; Cong Dong; Guoneng Li; Yousheng Xu; Qinhui Wang (Fuel, 2023)

In-situ crosslinked, side chain polybenzimidazole-based anion exchange membranes for alkaline direct methanol fuel cells - Guoliang Liu; Ailian Wang; Wenxi Ji; Fangfang Zhang; Jianing Wu; Taoyi Zhang; Haolin Tang; Haining Zhang (Chemical Engineering Journal, 2023)

Understanding the doping effect in CsPbI2Br solar cells: crystallization kinetics, defect passivation and energy level alignment - Haoyu Wang; Ze Wang; Xinyu Tang; Li Liu; Haolin Zhang; Xianghua Yao; Furong Wang; Shuanghong Wu; Xiaodong Liu (Chemical Engineering Journal, 2023)

Potential-dependent reconstruction of Ni-based cuboid arrays for highly efficient hydrogen evolution coupled with electro-oxidation of organic compound - Ruchun Li; Panyong Kuang; Swelm Wageh; Ahmed A. Al-Ghamdi; Haolin Tang; Jiaguo Yu (Chemical Engineering Journal, 2023)

Comparison of 16S rRNA Gene Primers on Studying Microbial Community Composition in Bottom Water and Sediment of Artificial Reefs in Laoshan Bay, China - Guangjie Fang; Haolin Yu; Huaxiang Sheng; Yanli Tang; Zhenlin Liang (Journal of Ocean University of China, 2022)

Impact of summer moratorium on set-net fishery in Haizhou Bay, China - Guangjie Fang; Haolin Yu; Xinmeng Wang; Huaxiang Sheng; Yanli Tang; Changdong Liu; Chuanxi Chen; Zhenlin Liang (Journal of Oceanology and Limnology, 2022)

Relationships Between Community Structure and Environmental Factors in Xixiakou Artificial Reef Area - Haolin Yu; Wenzhao Yang; Changdong Liu; Yanli Tang; Xiefa Song; Guangjie Fang (Journal of Ocean University of China, 2020)

Behavior and mechanism of low-concentration rare earth ions precipitated by the microbial humic-like acids - Junfeng Wang; Hai Li; Linwang Tang; Changming Zhong; Yaqi Liu; Liuxian Lu; Tingsheng Qiu; Haolin Liu (Environmental Science and Pollution Research, 2020)

Assessment of ECMWF reanalysis data in complex terrain: Can the CERA‐20C and ERA‐Interim data sets replicate the variation in surface air temperatures over Sichuan, China? - Haolin Luo; Fei Ge; Kangquan Yang; Shoupeng Zhu; Ting Peng; Wenyue Cai; Xiaoran Liu; Weiwei Tang (International Journal of Climatology, 2019)
Surface air temperatures (SATs) derived from the European Centre for Medium‐Range Weather Forecasts (ECMWF) ERA‐Interim and CERA‐20C reanalysis data sets are compared with data from 43 observation stations in Sichuan for 1979–2010. The results show (a) the temperatures from the ERA‐Interim and CERA‐20C data sets are strongly correlated with those from the observation stations, although significant cold biases are seen on both annual and seasonal timescales. (b) The biases in SATs are predominately influenced by the differences between the actual topography and the topography used in the reanalysis models. Larger differences in temperature are observed in the plateau and mountainous regions of Sichuan. We confirmed larger SAT biases at high altitudes by categorizing the elevation into four bands, each with a spacing of 1,000 m. (c) We reduced the biases resulting from elevation by using an elevation correction method with internal lapse rates derived from different reanalysis pressure levels. The annual mean bias was reduced from −2.86 to −0.75°C for the ERA‐Interim data set and from −5.27 to −2.21°C for the CERA‐20C data set. After calibration, the correlation coefficients between the difference in SAT (observed minus reanalysis data) and the difference in elevation (station elevation minus model elevation) decreased from −0.97 and −0.91 to −0.29 and −0.30 for the ERA‐Interim and CERA‐20C data sets, respectively. These significant differences should not be ignored in the application of reanalysis data sets to climate research. The evaluation and calibration of reanalysis data sets are essential before making assessments of regional climate change, especially over regions with complex topography.